The Role of Communication in Building Social relations with Deaf Persons - Beha, Admira (Technium Social Sciences Journal, 2020)
The communication isolation to which deaf people are exposed often influences the building of social relations and determines their social position. The paper presents research on the position of deaf people caused by communication and social factors. The sample consisted of deaf (n=127) and hearing (n=99) respondents. In the evaluation of the results was used descriptive and factor analysis. The research isolated communication discriminatory factors and factors of discrimination in the evaluation of social functions, based on which it can be concluded that communication plays a key role in building social relations of deaf people, but also that their position is conditioned stereotypical and discriminatory attitudes of the hearing environment.